A method of biodegrading keratinaceous material. - Syed, Mohd Arif (2010)

(untitled)
The invention provides a method of biodegrading keratinaceous material such as feathers wherein the method includes the steps of (a) combining the keratinaceous material with Bacillus sp. strain khayat or a mutant thereof in a feather basal salt media; and (b)incubating the mixture from step (a) to degrade the keratinaceous material. The aqueous feather basal salt media used in this process includes a salt mixture of 0.05% (w/v) sodium chloride, 0.07% (w/v) potassium dihydrogen phosphate, 0.14% (w/v) potassium hydrogen phosphate, 0.001% (w/v) magnesium sulphate and 1.0% (w/v) feather as nitrogen and carbon sources and adjusted to pH 7.2. The Bacillus sp. strain khayat or a mutant thereof is capable of degrading keratin and obtained from either an axenic culture, freeze-dried culture or pure culture of the said microorganism. The end-product of feather degradation can be used in the feed industry and the method as provided is sustainable, environmentally friendly and cost-effective.